Australian and New Zealand social workers adjusting to the COVID-19 pandemic. (1st August 2021) - Alston, Margaret; Irons, Kelly; Adamson, Carole; Boddy, Jenny; Fronek, Patricia; Briggs, Lynne; Hay, Kathryn; Howard, Amanda; Rowlands, Allison; Hazeleger, Tricia; Foote, Wendy
Abstract: In 2020, social workers across the world responded to the global COVID-19 pandemic and the consequent strict lockdown procedures over several months. In many countries, including Australia and New Zealand, this virtual shutdown period necessitated a reframing of social work practice to incorporate factors including delivery of services via virtual means and more limited access for vulnerable clients. This article draws on the integration of two methods designed to address the research question: 'How has social work practice in Australia and New Zealand been affected by COVID-19?' These include (i) a narrative review of papers published during 2020 on social work practice and the COVID-19 pandemic and (ii) an online survey, undertaken from October to December 2020, of Australian and New Zealand social workers. The questionnaire data were analysed using Statistical Package for the Social Sciences (SPSS) and thematic analysis. The findings of this article details include the significant impacts of COVID-19 on practice, the increased needs of clients, including a rise in health issues, violence, homelessness and financial concerns, and the resulting critical changes to social work workloads. Social workers also reported greater use of technologies to deliver services and fears for their families and themselves if exposed to COVID-19. Abstract : This article examines how Australian and New Zealand social workers have adjusted to the COVID-19 pandemic. The article draws on a literature review of international social work papers published during 2020 and a survey of social workers in Australia and New Zealand to determine the impacts on social workers. We find there are similarities in responses noted by social workers across the world including the enhanced use of technologies, difficulties supporting vulnerable clients and personal impacts in both work and home environments. There are also differences brought about by Australian and New Zealand social workers' prior experiences of disasters as well as issues with technology.